High Glass‐Transition Temperature Polymer Networks Harnessing the Dynamic Ring Opening of Pinacol Boronates. (25th July 2019) - Brunet, Juliette; Collas, Franck; Humbert, Matthieu; Perrin, Lionel; Brunel, Fabrice; Lacôte, Emmanuel; Montarnal, Damien; Raynaud, Jean
Abstract: Differential scanning calorimetry of high molar mass poly(4‐vinylphenylboronic acid, pinacol ester)s evidenced unusual reactive events above 120 °C, resulting in a high glass‐transition temperature of 220 °C. A reversible ring‐opening reactivity of pinacol boronates is proposed, involving a nucleophilic attack on the sp 2 boron and subsequent bridging between boron atoms by interconnected pinacol moieties to form a densely crosslinked network with high Tg . FTIR, solid‐state NMR investigations, and rheology studies on the polymer as well as double‐tagging analyses on molecular model structures and theoretical calculations further support this hypothesis and indicate a ring‐opening inducing crosslinking. When diluted in an apolar solvent such as toluene, the polymer network can be resolubilized via ring closing, thus recovering the entropically favored linear chains featuring cyclic boronate esters. Abstract : Polymere auf Styrolbasis mit anhängenden Pinakolboronatestergruppen vernetzen sich zu dichten Netzwerken mit Glasübergangstemperaturen von bis zu 220 °C. Die Vernetzung basiert auf einer bislang übersehenen dynamischen Ringöffnung cyclischer Boronate, die die Brückenbildung zwischen Boratomen fördert, und ist beim Verdünnen bei Umgebungstemperatur vollständig reversibel.